1985
DOI: 10.1016/0378-1097(85)90107-7
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of redox-indicator dyes in strongly reduced media; their effect on the human fecal flora

Abstract: Cresyl violet acetate was found to be an appropriate redox‐indicator dye in anaerobic culture media with low redox potentials. Low redox potentials (E′h−250 to −300 mV) in media were obtained by addition of dithiothreitol (DTT). DTT and cresyl violet acetate in media did not influence the total number of anaerobes cultured from human feces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Anaerobic conditions were verified by using the indicator resazurin (0-0002%), which becomes pink at a redox potential greater than -120 mV at pH 7-0. 15 After three days of incubation at 370C the colonies were counted. The flora was determined according to methods used in previous work on flora composition.…”
Section: Anaerobic Culturementioning
confidence: 99%
“…Anaerobic conditions were verified by using the indicator resazurin (0-0002%), which becomes pink at a redox potential greater than -120 mV at pH 7-0. 15 After three days of incubation at 370C the colonies were counted. The flora was determined according to methods used in previous work on flora composition.…”
Section: Anaerobic Culturementioning
confidence: 99%
“…Resazurin dye (Acros Organic, New Jersey) was used as an indicator of redox state and does not affect in vitro digestion [32]. For all active digestions, resazurin dye added to active rumen solutions remained colorless throughout the incubation, indicating highly-reduced, anaerobic conditions prevailed.…”
Section: Methodsmentioning
confidence: 99%
“…Replacement of resazurine by Janus Green B as a redox indicator (E~ = 260 mV [18]) revealed that dithionite poised the redox potential (E h) of the cultures at a value of less than -300 mV [18]. After approximately 6 hours the culture E h increased to a more positive value than 300 inV.…”
Section: The Effect Of Dithionite On the Growth Ofmentioning
confidence: 99%